SPE Annual Technical Conference and Exhibition 2005
DOI: 10.2118/97190-ms
|View full text |Cite
|
Sign up to set email alerts
|

Horizontal-Well Productivity Equations With Both Uniform-Flux and Uniform-Pressure Wellbore Modes

Abstract: TX 75083-3836, U.S.A., fax 01-972-952-9435. AbstractThis paper concerns the estimation of pseudosteady-state horizontal-well productivity with emphasis on handling two types of wellbore conditions: uniform-flux and uniformpressure. We present rigorous (analytically) and simplified PI (productivity index) equations which can easily handle the above two wellbore conditions within a consistent framework.The presented simplified PI equations were verified successfully (i) through detailed mathematical/physical ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
3

Year Published

2007
2007
2011
2011

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 6 publications
1
8
0
3
Order By: Relevance
“…The largest error is 8.7% for the reservoir with an aspect ratio of two. In all cases, the calculated PI for a fracture length of 0.9 is larger than the maximum possible PI for a completely penetrating fracture, confirming the calculations of Chen and Asaad (2005).…”
Section: Ep Methodssupporting
confidence: 78%
See 1 more Smart Citation
“…The largest error is 8.7% for the reservoir with an aspect ratio of two. In all cases, the calculated PI for a fracture length of 0.9 is larger than the maximum possible PI for a completely penetrating fracture, confirming the calculations of Chen and Asaad (2005).…”
Section: Ep Methodssupporting
confidence: 78%
“…Recently, Chen and Asaad (2005) showed that the EP and AP methods produce significantly different productivities, particularly for medium and large fracture lengths. Generally, the productivity based on the EP method is larger and, in the case of long fractures, could even exceed the maximum theoretical productivity.…”
Section: Introductionmentioning
confidence: 99%
“…Babu and Odeh (1988) proposed (Chen and Asaad, 2005;Economides et al, 1991;Giger, 1985;Helmy and Wattenbarger, 1998;Joshi, 1986;Lu and Tiab, 2007;Mutalik and Godbole, 1988). A comprehensive review of productivity indexes was created by Choi et al (2008).…”
Section: Current Oilfield Assumptionsmentioning
confidence: 99%
“…The DVS method has been validated through comparison with existing analytical models for determining pressure distributions caused by various sink configurations (Gringarten et al 1974;Ozkan 1988;Yildiz and Bassiouni 1990;Cinco-Ley et al 1978;Cinco-Ley and Meng 1988) and for determining productivities of simple completion schemes (Babu and Odeh 1989;Goode and Kuchuck 1991;Chen and Asaad 2005). Comparisons provided by Amini (2007) also include results obtained with a numerical reservoir simulator for a system of a horizontal well with multiple transverse fractures.…”
Section: Problem Backgroundmentioning
confidence: 99%